Ghrelin Receptor in Two Species of Anuran Amphibian, Bullfrog (Rana catesbeiana), and Japanese Tree Frog (Hyla japonica) - Kaiya, Hiroyuki; Koizumi, Yasushi; Konno, Norifumi; Yamamoto, Kazutoshi; Kangawa, Kenji; Miyazato, Mikiya (Frontiers in Endocrinology, 2011)
We identified cDNA encoding a functional growth hormone secretagogue-receptor 1a (GHS-R1a, ghrelin receptor) in two species of anuran amphibian, bullfrog (Rana catesbeiana) and Japanese tree frog (Hyla japonica). Deduced receptor protein for bullfrog and Japanese tree frog (tree frog) was comprised of 374- and 371-amino acids, respectively. The two receptors showed 86% identity with each other, and phylogenetic analysis revealed that the two receptors belong to the same category with tetrapods. In functional analyses, ghrelin and GHS-R1a agonists increased intracellular Ca2+ concentration in HEK293 cell that transfected each receptor cDNA, but ligand selectivity of ghrelin with Ser3 and Thr3 was not observed between the two receptors. Bullfrog GHS-R1a mRNA was mainly expressed in the brain, stomach and testis. In the brain, the gene expression was detected in the diencephalon and mesencephalon, but not in the pituitary. Tree frog GHS-R1a mRNA was predominantly expressed in the gastrointestinal tract and ovary, but not detected in the pituitary. In bullfrog stomach, GHS-R1a mRNA expression increased at 10 days after fasting, but not in the brain. In tree frog, GHS-R1a mRNA expression increased in the brain, stomach and ventral skin by 10-days fasting, and in the stomach and ventral skin by a dehydration treatment. Intracerebroventricular injection of ghrelin in dehydrated tree frog did not affect water absorption from the ventral skin. These results suggest that ghrelin is involved in energy homeostasis and possibly in osmoregulation in frogs.